Designing networked learning with 4Ts - Pozzi, Francesca; Ceregini, Andrea; Persico, Donatella (Proceedings of the International Conference on Networked Learning, 2016)
This paper tackles the issue of how to support the design of effective collaborative activities in networked learning contexts. At the crossover between the ‘learning design' and the ‘networked learning' research sectors, notions such as ‘collaborative techniques', ‘design patterns' or ‘scripts' are often used to describe and/or run online collaborative learning activities. Based on these concepts, technological tools have been implemented that reify these notions and support several phases of the learning design process, including the sharing and reuse of design representations. Despite the differences among tools, most of the them support the representation of learning designs that are already "in the designer's mind", while few technological tools specifically provide guidance and support in the early phase of the design process of collaborative activities, i.e. the conceptualization of the design. Focusing on this gap, this paper proposes a model and, based on it, a game supporting the conceptualization of online collaborative activities for networked learning contexts. Both the model and the game are based on the interplay of four variables, the 4Ts: Task, Teams, Time and Technology, regarded as the key aspects of the decisions to be made. The model suggests that, to design the online activity, the teacher/designer will need to "juggle" around with these four variables and their reciprocal relationships in a cyclic, iterative process, regardless of whether she wants to start the design from scratch or to reuse an already existing collaborative. Implemented with the aim of scaffolding such iterative process and supporting a group of teachers in the decision taking phases, the game consists of a board, representing the Time component, and of 5 decks of cards (respectively for the Task, Team, Technology, Technique and the Jokers). Each deck contains cards describing instances of Task, Team, Technology or Technique, while the Joker cards are empty and should be filled in by players with new instances. To guide the decisions, each card illustrates the dependencies between that particular instance of T and the others, thus making the decision criteria as explicit as possible and stimulating reflection on how each variable impacts on the others. Both the 4Ts model and the game have been field tested and evaluated by the developers with a group of 48 teachers. The results encourage the development of a digital version of the game, where cards are still tangible objects, and augmented reality techniques are employed to digitize the results of conceptualisation.